A Comparative Study Of Growth, Metabolism And Digestive Enzyme Activities Of Pinealectomized And Non-Pinealectomized Catfish (Heteropneustes Fossilis) - Rani, Sudesh (Zenodo, 2018)
A 60 days experiment was done to find out the importance of melatonin hormone dose on growth and metabolism of pinealectomized and non-pinealectomized catfish Heteropneustes fossilis. Experimental fish were fed with laboratory prepared formulated feed. All the experimental fish were having the mean body weight of 5-20 g was divided into two groups, pinealectomized and non-pinealectomized. Each group has two replicates. Melatonin injection of 25 and 50 mg were given to both the groups. Results of the present study indicated that Melatonin injected catfish of non-pinealectomized group shows maximum growth as compared to catfish received melatonin in pinealectomized group. The specific growth rate (SGR) and protein efficiency ratio (PER) values were higher in non-pinealectomized catfish as compared to pinealectomized catfish. However, the FCR valued were increased in melatonin received pinealectomized group as compared to melatonin administered non-pinealectomized group of catfish. The biometric indexes, hepatosomatic index (HSI) and viscerosomatic index (VSI) recorded maximum in pinealectomized fish as compared to non-pinealectomized catfish. Also, the digestive enzyme activities (protease, amylase, cellulase and lipase) were increased in melatonin administered non-pinealectomized catfish as compared melatonin injected pinealectomized catfish. The value for glycogen content in muscle was recorded higher in melatonin receiving pinealectomized fishes however the glycogen content in liver shows maximum values in melatonin receiving non-pinealectomized catfish. The results of this experiment showed that melatonin administered non-pinealectomized fish resulted in an increased growth, metabolism and digestive enzyme activities as compared to melatonin receiving pinealectomized catfish. : {"references": ["Alam, M. S., Jahan, M., Hossain, M. M., & Islam, M. S. (2009). Population genetic structure of three major river populations of rohu, Labeo rohita (Cyprinidae: Cypriniformes) using microsatellite DNA markers. Genes & Genomics, 31(1), 43-51.", "Alok, D., Krishnan, T., Talwar, G., & Garg, L. C. (1993). Induced spawning of catfish, Heteropneustes fossilis (Bloch), using D-Lys6 salmon gonadotropin-releasing hormone analog. Aquaculture, 115(1-2), 159-167.", "Aripin, S.A., Jintasataporn, O., & Yoonpundh, R. Effects of Melatonin on Clarias Macrocephalus Female Broodstock Performance. International Journal of Sciences: Basic and Applied Research 21(1), 129-137.", "AOAC, 1995. Official methods of analysis of the Association of Official Analytical Chemist. 15th eds., Washington, D.C., 1 and 2, 1298.", "Benyassi, A., Schwartz, C., Coon, S. L., Klein, D.C., & Falcon, J. (2000). Melatonin synthesis: arylalkylamine N\u2010acetyltransferases in trout retina and pineal organ are different. Neuroreport, 11(2), 255-258.", "Bhatt, V. (1968). Studies on the biology of some freshwater fishes. Part VII. Heteropneustes fossilis, 99-115.", "Collin, J.P. (1971). Differentiation and regression of the cells of the sensory line in the epiphysis cerebri. The pineal gland, 79-125.", "Colowick, S.P. and Kaplan, N.O., 1955. Methods of enzymology. Academic Press, New York., 1, 627", "Coon, S. L., Begay, V., Deurloo, D., Falcon, J., & Klein, D.C. (1999). Two arylalkylamine N-acetyltransferase genes mediate melatonin synthesis in fish. Journal of Biological Chemistry, 274(13), 9076-9082.", "De Pedro, N., Mart\u00ednez Alvarez, R. M., & Delgado, M. (2008). Melatonin reduces body weight in goldfish (Carassius auratus): effects on metabolic resources and some feeding regulators. Journal of pineal research, 45(1), 32-39.", "Delahunty, G., & Tomlinson, M. (1984). Hypoglycemic effects of melatonin in the goldfish, Carassius auratus. Comparative Biochemistry and Physiology Part A: Physiology, 78(4), 871-875.", "Falcon, J. (1999). Cellular circadian clocks in the pineal. Progress in neurobiology, 58(2), 121-162.", "Falcon, J., Gothilf, Y., Coon, S., Boeuf, G., & Klein, D. (2003). Genetic, temporal and developmental differences between melatonin rhythm generating systems in the teleost fish pineal organ and retina. Journal of Neuroendocrinology, 15(4), 378-382.", "FAO, & WFP (2014). The state of food insecurity in the world, 80.", "Lopez Olmeda, J., Madrid, J., & Sanchez Vazquez, F. (2006). Melatonin effects on food intake and activity rhythms in two fish species with different activity patterns: diurnal (goldfish) and nocturnal (tench). Comparative Biochemistry and Physiology Part A: Molecular and Integrative Physiology, 144(2), 180-187.", "Nguyen, N., Stellwag, E. J., & Zhu, Y. (2008). Prolactin-dependent modulation of organogenesis in the vertebrate: recent discoveries in zebrafish. Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 148(4), 370-380.", "Porter, M., Randall, C., Bromage, N., & Thorpe, J. (1998). The role of melatonin and the pineal gland on development and smoltification of Atlantic salmon (Salmo salar) parr. Aquaculture. 168(1-4), 139-155.", "Radhakrishnan, M., & Sugumaran, E. (2010). Effect of Sugarcane Bagasse and Supplemental Feed on Certain Reproductive Characterestics of the Catfish Heteropneustes fossilis (Bloch.). Journal of Fisheries International, 5(4), 58-60.", "Rani, S. and Sabhlok, V.P., 2014. Effect of melatonin administration on growth and metabolism of catfish Clarias batrachus under different photoperiods. Journal of International Academic Research for Multidisciplinary, 2, 627-635.", "Saha, N., & Ratha, B. (1998). Ureogenesis in Indian air-breathing teleosts: adaptation to environmental constraints. Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 120(2), 195-208.", "Sevier, H., Raae, A.J. and Lied, E., 2000. Growth and protein turnover in (Atlantic samo salar L.) the effect of dietary protein level and protein particle size. Aquaculture. 185, 101-120.", "Singh, R., Singh, A., & Tripathi, M. (2012). Melatonin induced changes in specific growth rate, gonadal maturity, lipid and protein production in Nile tilapia Oreochromis niloticus (Linnaeus 1758). Asian-Australasian Journal of Animal Sciences, 25(1), 37.", "Taylor, J., Migaud, H., Porter, M., & Bromage, N. (2005). Photoperiod influences growth rate and plasma insulin-like growth factor - I levels in juvenile rainbow trout, Oncorhynchus mykiss. General and Comparative Endocrinology, 142(1-2), 169-185.", "Thakur, N. K. (1991). Possibilities and problems of catfish culture in India Journal Inland Fish Society of India, 23(2), 80-90.", "Zhang, C., Yang, X.Z., Xu, M.J., Huang, G.Y., Zhang, Q., Cheng, Y.X., Ren, H.Y. (2018). Melatonin Promotes Cheliped Regeneration, Digestive Enzyme Function, and Immunity Following Autotomy in the Chinese Mitten Crab, Eriocheir sinensis. Frontiers in Physiology, 9, 269."]}